Complete blood count derived inflammatory biomarkers and the level of anti-SARS-CoV-2 NAb and S-RBD IgG among cancer survivors receiving COVID-19 vaccines. Issue 2 (April 2023) - Mulansari, Andhika Rachman Nadia Ayu; , Anggraini Iriani; Lubis, Anna Mira; Rumondor, Bayu Bijaksana
No abstract available